The effect of pretreatment on methanesulfonic acid-catalyzed hydrolysis of bagasse to levulinic acid, formic acid, and furfural. Issue 78 (5th August 2016) - Rackemann, Darryn W.; Bartley, John P.; Harrison, Mark D.; Doherty, William O. S.
Abstract : Pretreatment increases levulinic acid yields in acid catalysed hydrolysis of bagasse using low corrosive methanesulfonic acid. Abstract : A major challenge that must be overcome for the commercial production of levulinic acid from lignocellulosics is to reduce equipment blockage and corrosion. Methanesulfonic acid (MSA), a relatively low corrosive acid, was used to produce organic acids and furfural from pretreated sugarcane bagasse. In general, the type of pretreatment did not affect levulinic acid yield, though it affected furfural yield. However, soda pretreated bagasse produced the highest yields of levulinic acid (∼75 mol%) and furfural (∼85 mol%), albeit under optimized conditions. Hydrolysis residue consists primarily of lignin that has been modified and/or condensed to humic substances, fatty acids, and oligomeric sugars. A conceptual biorefinery utilizing 1 ton of dry bagasse, alkaline-pretreatment, and MSA as a catalyst produced 165 kg soda lignin, 190 kg and 89 kg of levulinic acid and formic acid respectively, and 40 kg furfural.